Advanced environmental exercise physiology - Cheung, Stephen S; Ainslie, Philip N. (Champaign, Illinois Human Kinetics, 2022)
Advanced Environmental Exercise Physiology, Second Edition, offers a complete look at the major topics and debates in the field of environmental exercise physiology. In this second edition, Dr. Stephen Cheung is joined by the coauthor Dr. Phil Ainslie, who has extensive research and professional expertise in mountaineering and high-altitude physiology. Among the issues explored in this text are the effects of heat, hydration, and cold in the thermal environment; diving, altitude training, and other pressure effects on the human system; and the influences that pollution and air quality have on exercise. The text also explores the microgravity (space) environment and chronobiological rhythms. The second edition includes new chapters on heat adaptation and therapy, breath-hold diving, physiological adjustments to acute hypoxia, sex differences to environmental stressors, and cross-adaptation. Advanced Environmental Exercise Physiology, Second Edition, will teach readers the following: • The initial physiological responses upon exposure to an environment that a person is not adapted to • How the body adapts to repeated exposure to an environment • How various environments affect the ability to exercise and work • Individual variability in response to stressful environments Supported by evidence-based information and numerous references, Advanced Environmental Exercise Physiology, Second Edition, addresses the primary environmental factors affecting people when they are working, exercising, and competing in sport. Ancillaries for adopting instructors are available online
Keywords: Exercise -- Physiological aspects; Adaptation (Physiology)